2020
DOI: 10.3390/cells9020370
|View full text |Cite
|
Sign up to set email alerts
|

Blood Contamination in CSF and Its Impact on Quantitative Analysis of Alpha-Synuclein

Abstract: Analysis of cerebrospinal fluid (CSF) is important for diagnosis of neurological diseases. Especially for neurodegenerative diseases, abnormal protein abundance in CSF is an important biomarker. However, the quality of CSF is a key factor for the analytic outcome. Any external contamination has tremendous impact on the analysis and the reliability of the results. In this study, we evaluated the effect of blood contamination in CSF with respect to protein biomarker identification. We compared three distinct mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Hypothetically, the presence of Lewy bodies (a common co-pathology in AD patients) could reduce CSF α-synuclein (as in PD), while the presence of synaptic or neuronal degeneration could increase CSF α-synuclein as an injury response 97 . A pre-analytical factor affecting CSF αsynuclein is that it is sensitive to blood-contamination, which gives false high levels 98 . The inconsistent results, the unclear biological role, and the pre-analytical variability may make it difficult to apply CSF α-synuclein as a biomarker.…”
Section: Levels Of Reproducibilitymentioning
confidence: 99%
“…Hypothetically, the presence of Lewy bodies (a common co-pathology in AD patients) could reduce CSF α-synuclein (as in PD), while the presence of synaptic or neuronal degeneration could increase CSF α-synuclein as an injury response 97 . A pre-analytical factor affecting CSF αsynuclein is that it is sensitive to blood-contamination, which gives false high levels 98 . The inconsistent results, the unclear biological role, and the pre-analytical variability may make it difficult to apply CSF α-synuclein as a biomarker.…”
Section: Levels Of Reproducibilitymentioning
confidence: 99%
“…Thus, blood contamination during CSF acquisition might represent another source of variation, skewing the t-α-syn concentration results in CSF. 183,184 Despite the possible problems just discussed, there have been many studies evaluating α-syn as blood biomarker for dementias. Studies for α-syn in plasma and serum in PD have all shown similar conflicting results as in CSF.…”
Section: Pre-and Postsynaptic Biomarkersmentioning
confidence: 99%
“…Thus, blood contamination during CSF acquisition might represent another source of variation, skewing the t-α-syn concentration results in CSF. 183 , 184 …”
Section: Fluid Biomarkers For Synapse Pathologymentioning
confidence: 99%
“…To this end, probes specifically targeting o-␣Syn with high sensitivity and high affinity hold great promise [214]. Of note, it is important to indicate here that higher CSF ␣Syn concentrations can be linked to blood contamination due to the expression of ␣Syn in erythrocytes [215], thereby requiring strict and rigorous markers for blood contamination and/or a standardized grade system for blood levels in CSF samples. Studies are also being performed to find molecules blocking the endocytosis of ␣Syn oligomers, thus preventing healthy cells from taking up pathogenic ␣Syn species, which could serve as a potential strategy for reducing oligomeric ␣Synmediated toxicity [214].…”
Section: Monotherapymentioning
confidence: 99%